Putting on a show; Collecting, exhibiting, and performing wayang at the Tropenmuseum from colonial times until the present - Boonstra, Sadiah (UI Scholars Hub, 2019)
The Tropenmuseum in Amsterdam has a rich history in collecting, exhibiting, and presenting wayang performances. This paper traces this history of collection, exhibition, and performance practice of wayang at the Colonial Institute, from 1950 known as Tropenmuseum in Amsterdam, the Netherlands, from colonial times until the present. It demonstrates the entanglement of colonial and postcolonial power structures, collection, and exhibition legacies of the colonial past. The paper will show that from the moment wayang puppets entered the museum’s collection there has been continuous interaction between collecting and exhibition practices and performance practices. The emphasis on tangible elements of performance practice in collection and exhibition practices contributed to a dominant and static understanding of wayang.